Discovery of Small-Molecule Inhibitors Targeting the E3 Ubiquitin Ligase Activity of the Herpes Simplex Virus 1 ICP0 Protein Using an In Vitro High-Throughput Screening Assay - Deschamps, Thibaut (J Virol, 2019)
Herpes simplex virus 1 (HSV-1) has infected more than 80% of the population. Reactivation of the virus causes diseases ranging in severity from benign cold sores to fatal encephalitis. Current treatments involve viral DNA replication inhibitors, but the emergence of drug-resistant mutants is observed frequently, highlighting the need for novel antiviral therapies. Infected cell protein 0 (ICP0) of HSV-1 is encoded by an immediate early gene and plays a fundamental role during infection, because it enables viral gene expression and blocks antiviral responses. One mechanism by which ICP0 functions is through an E3 ubiquitin ligase activity that induces the degradation of targeted proteins. A ΔICP0 virus or mutants with deficiencies in E3 ligase activity cannot counteract beta interferon (IFN-β)-induced restriction of viral infection, are highly immunogenic, are avirulent, and fail to spread. Thus, small molecules interfering with essential and conserved ICP0 functions are expected to compromise HSV-1 infection. We have developed a high-throughput screening assay, based on the autoubiquitination properties of ICP0, to identify small-molecule inhibitors of ICP0 E3 ubiquitin ligase activity. Through a pilot screening procedure, we identified nine compounds that displayed dose-dependent inhibitory effects on ICP0 but not on Mdm2, a control E3 ubiquitin ligase. Following validation, one compound displayed ICP0-dependent inhibition of HSV-1 infection. This compound appeared to bind ICP0 in a cellular thermal shift assay, it blocked ICP0 self-elimination, and it blocked wild-type but not ICP0-null virus gene expression. This scaffold displays specificity and could be used to develop optimized ICP0 E3 ligase inhibitors. IMPORTANCE Since acyclovir and its derivatives were launched for herpesviruses control almost four decades ago, the search for novel antivirals has waned. However, as human life expectancy has increased, so has the number of immunocompromised individuals who receive prolonged treatment for HSV recurrences. This has led to an increase in unresponsive patients due to acquired viral drug resistance. Thus, novel treatments need to be explored. Here we explored the HSV-1 ICP0 E3 ligase as a potential antiviral target because (i) ICP0 is expressed before virus replication, (ii) it is essential for infection in vivo, (iii) it is required for efficient reactivation of the virus from latency, (iv) inhibition of its E3 ligase activity would sustain host immune responses, and (v) it is shared by other herpesviruses. We report a compound that inhibits HSV-1 infection in an ICP0-dependent manner by inhibiting ICP0 E3 ligase activity.